2020
DOI: 10.21432/cjlt27890
|View full text |Cite
|
Sign up to set email alerts
|

Does the Association of Social Media Use with Problematic Internet Behaviours Predict Undergraduate Students Academic Procrastination?

Abstract: Researchers are of the view that students’ attachment to social media may lead to negative consequences such as postponement of their academic work. Yet how social media use is associated with academic procrastination of students is still underexplored. This study ascertained the pathways through which social media use predicted academic procrastination of undergraduate students. The sample size comprised 500 year one students of the Faculty of Education, Nnamdi Azikiwe University, Awka. Path analysis was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
3
9
0
6
Order By: Relevance
“…Most students get carried away and distracted from properly using social media for academic purposes. The finding of this study corroborates with the existent findings that social media addiction has a positive relationship with academic procrastination (Nwosu et al, 2020;Hayat et al, 2020;Uztermur, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Most students get carried away and distracted from properly using social media for academic purposes. The finding of this study corroborates with the existent findings that social media addiction has a positive relationship with academic procrastination (Nwosu et al, 2020;Hayat et al, 2020;Uztermur, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Academic procrastination plays a significant role in the context of social media addiction among students in this new normal education, which impacts their educational progress. Other studies are related to this finding (Uztermur, 2020;Nwosu et al, 2020;Koppenborg & Klingsieck, 2022;Kryshko et al, 2022;Cemiloglu et al, 2022).…”
Section: Discussionsupporting
confidence: 57%
“…Besides, during this new normal education, students perceived an inability to manage their time spent on social media platforms and the amount of time spent on platforms for academic purposes. Furthermore, internet addiction was connected with academic procrastination among learners (Karatas, 2015;Azizi et al, 2019;Nwosu et al, 2020). Meanwhile, Hayat et al (2020) also discovered a significant association between internet addiction and academic procrastination among Shiraz University medical students.…”
Section: Social Media Addictionmentioning
confidence: 99%
“…Given the detrimental effects of social media use on academic procrastination, empirical studies show that social media addiction and academic procrastination were substantially linked and positively correlated (Üztemur, 2020). The level of social media addiction is thought to be a predictor of academic procrastination, as it has been suggested that social media use may not promote academic procrastination until one becomes addicted to social media (Nwosu et al, 2020).…”
Section: Social Media Addiction and Academic Procrastinationmentioning
confidence: 99%